عوامل تكوين الحافظ ابن حجر العسقلاني العلمية: The Scientific Factors of the Formation of al-Hafiz Ibn Hajar al-Asqalani Scholarship (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
Al-Hafiz Ibn Hajar Al-Asqalani is considered to be one of the most famous scholars of hadith in his time and the time after him. He has many compilations in hadith sciences which comprise different topics. He has a unique approach when dealing with the Hadith of Rasulullah SAW, with hadith sciences, and generally with Muslims. This research deals with the factors that have developed his character and intellect. His method was through reading and researching all of the related topics which subsequently had made his compilations to be placed at a prestigious level, and made him distinctive from his peers. He is brilliant, knowledgeable, has a photographic memory, and has spent his life in seeking knowledge, devoted to scholars and their classes, obtaining knowledge, and has benefitted from prominent scholars of his time; in which Allah SWT had prepared him for the Islamic sciences. Notably, Al-Hafiz Ibn Hajar had lived in the era of the Mamluk state, when the Islamic sciences had reached its summit and flourished, and many scholars were produced.